Determinação da soroprevalência da infecção pelo vírus da hepatite e na cidade de São Paulo - Reinaldo, Monica Renata [UNIFESP] (2016)
Introduction: Hepatitis E virus infection currently accounts for over 50% of acute hepatitis cases in endemic areas. Liver failure can occur in patients with other underlying liver diseases or women on the third trimester of pregnancy, as well as the chronic form of the disease, especially solid organ transplanted patients. Objectives: To determine the seroprevalence of HEV infection in the city of São Paulo, through the detection of anti-HEV IgG and IgM antibodies, and in the positive samples the detection of RNA-HEV presence by real time RT-PCR. Methods: 500 blood donors of the Benevolent Association of Blood Collection, in the city of São Paulo, Brazil were included in the study from July to September 2014. Samples were categorized according to gender, age and geographic region following a sampling plan. The detection of anti-HEV IgG and IgM anti-HEV antibodies was performed by enzyme immunoassay Wantai (Beijing Wantai Biological Pharmacy Enterprise, Beijing, China). Samples that were "reagent" for anti-HEV IgG were subjected to viral RNA extraction and subsequent HEV RNA test using real time RT-PCR. Results: In total, 49 samples were positive for anti-HEV IgG, resulting in a seroprevalence of 9.8%. Of these, only one was positive for anti-HEV IgM. In none of these seropositive samples was HEV RNA detected. The age group between 45 to 59 years presented with 4 times the risk of past infection when compared to the age group of 18-29 years. The demographic regions Center and South Center showed an increased risk of 7 and 6 times, respectively, for the presence of anti-HEV IgG antibodies when compared to the Northeast region. Conclusions: The prevalence of HEV in blood donors in the city of São Paulo is the second highest prevalence in Brazil and the highest prevalence ever reported in the city of São Paulo.